Spatial Structure in Baiturrahman Context District (Banda Aceh) (International Journal of Architecture and Urbanism, 2020)
A city can be defined as a residential area and a place of activity for residents who dominate its spatial layout that is an area boundary, that is supported by appropriate facilities that are applied to the laws and regulations to help the lives of the people to be independent. To increase the development of the city, it is necessary to pay attention to the structure of the city space which is directed by the urban spatial plan which consists of the system of the city space and the pattern of the city space Banda Aceh is one of the cities that is the capital of the Aceh prevention, where one of the city centers is in Baiturrahman District where in the area there is a historical heritage in the form of the Baiturrahhman Grand Mosque which is the icon of the city of Banda Aceh and the Aceh province, the city of Banda Aceh itself, especially in the region. Baiturrahhman has met the service needs of both the trade, government, and education sectors, but it is still necessary to add additional facilities to support urban development in certain areas. The research method used to collect data is a descriptive qualitative method by collecting data and analyzing data. With the final result, where can we determine whether Baiturrahman District has fulfilled the spatial structure of city services in Banda Aceh?